Distinct and independent dielectrophoretic behavior of the head and tail of sperm and its potential for the safe sorting and isolation of rare spermatozoa. Issue 11 (15th April 2019) - Shuchat, Sholom; Park, Sinwook; Kol, Shahar; Yossifon, Gilad
Abstract: Often, in semen samples with minute amounts of sperm, even the single spermatozoon required to fertilize an oocyte cannot be found in the ejaculate. This is primarily because currently, sperm is generally searched for manually under a microscope. In this study, dielectrophoresis (DEP) was investigated as an alternative automated technique for sorting sperm cells. Using a quadrupolar electrode array it was shown that the head and tail of the sperm had independent and unique crossover frequencies corresponding to the transition of the DEP force from repulsive (negative) to attractive (positive). These surprising results were further analyzed, showing that the head and tail have their own distinct electrical properties. This significant result allows for the sperm's head, which contains the DNA, to be distanced from potentially damaging high electric fields using negative DEP while simultaneously manipulating and sorting the sperm using the positive DEP response of the tail. A proof of concept sorting chip was designed and tested. The low crossover frequency of the tail also allows for the use of a higher conductivity, and thus more physiological, medium than the conventional DEP solutions. Although more research is required to design and optimize an efficient, user‐friendly, and high‐throughput device, this research is a proof of concept that DEP has the potential to automate and improve the processing of semen samples, especially those containing only rare spermatozoa.